c-Type Cytochromes and Manganese Oxidation in Pseudomonas putida MnB1 - Caspi, Ron (American Society for Microbiology, 1998)
Pseudomonas putida MnB1 is an isolate from an Mn oxide-encrusted pipeline that can oxidize Mn(II) to Mn oxides. We used transposon mutagenesis to construct mutants of strain MnB1 that are unable to oxidize manganese, and we characterized some of these mutants. The mutants were divided into three groups: mutants defective in the biogenesis of c-type cytochromes, mutants defective in genes that encode key enzymes of the tricarboxylic acid cycle, and mutants defective in the biosynthesis of tryptophan. The mutants in the first two groups were cytochrome c oxidase negative and did not contain c-type cytochromes. Mn(II) oxidation capability could be recovered in a c-type cytochrome biogenesis-defective mutant by complementation of the mutation.